Model Identifikasi Risiko dan Strategi Peningkatan Nilai Tambah pada Rantai Pasok Kelapa Sawit - Syarif Hidayat; Marimin .; Ani .; Sukardi .; Mohamad Yani (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
The actors in the palm oil supply chain industry are the farmers, traders, crude palm oil (CPO) factories, frying-oil factories (refineries), distributors and the consumers. The farmers sell fresh fruit bunches (FFB) to the CPO factories through traders. FFB is converted into CPO which is later sold to the refineries. Refineries convert CPO into frying oil which is sold to the consumers through the distributors. There are risks due to product quality consistency, price fluctuation and supply chain continuity. This study has two objectives: (1) to develop a model to identify, evaluate and rank the risks, (2) to develop a model to identify and rank the strategies in improving their added value. Data for this study was obtained through direct interviews and questionnaires. The respondents were selected experts and industry players. The data were processed using Fuzzy Analytic Hierarchy Process (FAHP) models. The first FAHP model showed that the two most important risks were the supply chain continuity and product quality. The second FAHP model showed that the recommended strategies to improve the added values of the actors were the improvement of the infrastructure/cluster development, followed by the usage of superior seeds and cultivation techniques.